Proceedings of the International Conference on Science and Education and Technology 2018 (ISET 2018) 2018
DOI: 10.2991/iset-18.2018.114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nicotiana tabacum Extract Concentration as Biopesticide on protein content of Robusta coffee beans and skin

Abstract: Tobacco is a plantation commodity used as the main ingredient of cigarettes. Nicotiana tabacum extract as biopesticides are nicotine content, d-limonene, pyridine, and indole on tobacco used as pest control of plants. This study examined the Effect of Nicotiana tabacum Extract Concentration as Biopesticide on protein content of Robusta coffee beans and skin. The research was conducted in March until August 2017 at Kebondalem, Jambu, Semarang with altitude of 711 meters above sea level. The study was designed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Besides that, lemongrass leaves are repellent too [19] [20]. The bioactive compound of tobacco is nicotine, d-limonene, pyridine, and indole, which can be used as biopesticides because the compounds have a function as pesticides to control crop pests [21]. Table 5 showed that there was no significant difference between the application of inorganic pesticides and botanical pesticides.…”
Section: Pest Populationmentioning
confidence: 99%
“…Besides that, lemongrass leaves are repellent too [19] [20]. The bioactive compound of tobacco is nicotine, d-limonene, pyridine, and indole, which can be used as biopesticides because the compounds have a function as pesticides to control crop pests [21]. Table 5 showed that there was no significant difference between the application of inorganic pesticides and botanical pesticides.…”
Section: Pest Populationmentioning
confidence: 99%
“…109 tahun 2012 tentang Pengamanan Bahan yang mengandung zat adiktif berupa produk tembakau bagi kesehatan pasal 58 ayat 1 menyebutkan tentang "Upaya Pengembangan dalam Rangka Diversifikasi Produk Tembakau". Hal ini menunjukkan bahwa daun tembakau dapat dimanfaatkan lebih luas selain rokok seperti biopestisida, minyak atsiri, farmasi, parfum, bio-oil, bio-char, dan biogas (Dewi et al, 2018;Ruiz-Rodriguez et al, 2008;Kun et al, 2013). Salah satu produk daun tembakau yang dapat dimanfaatkan untuk masyarakat adalah dijadikan sebagai komponen aktif dalam pembuatan produk sediaan body soap.…”
Section: Pendahuluanunclassified
“…Tobacco is the main ingredient of cigarettes mostly found on the stubs, which is also one of the plantation commodities (Dewi et al, 2018). In the year 2006, Indonesia's cigarette consumption in the amount of 215 billion, while in the year 2010 estimated in the amount of 213 billion (Suharti et al, 2010).…”
Section: Introductionmentioning
confidence: 99%